The Effect Of Competence On Employee Performance On South Binjai Sub-District Office - Nila Rela Simanjuntak; Mesra B (Yayasan Multidimensi Kreatif, 2024)
This study aimed to analyze the relationship pattern between variables and examine the effect of two independent (exogenous) variables on the dependent variable. This type of research was a quantitative associative causal study. The study was conducted at the Camat Sidikalang Office, with a population of 48 employees. The sampling technique used was saturated sampling, which is a technique where all members of the population are selected as samples. The data used in this study were obtained from questionnaires distributed to respondents, consisting of all employees from all divisions. The results of the study showed that Kompetensi had a positive and significant effect on Employee Performance. This was evidenced by a t-count value of 5.731 > t-table value of 1.66827, and a significance value of 0.000 < 0.05. The regression coefficient of 0.606 indicated that every 1-point increase in Kompetensi would lead to an increase of 0.606 points in Employee Performance, assuming other variables remain constant. Furthermore, the coefficient of determination test results showed an Adjusted R Square value of 0.404 or 40.40%, indicating that Kompetensi had a relatively high effect on Employee Performance, with the remaining 59.60% being influenced by other factors not explored in this study. Overall, the findings of this study identified that increasing Kompetensi could contribute to improving Employee Performance at the Camat Sidikalang Office.